2013
DOI: 10.3171/2012.10.peds12307
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent pediatric central nervous system low-grade gliomas: the role of surveillance neuroimaging in asymptomatic children

Abstract: Object Pediatric low-grade glioma (LGG) is the most common brain tumor of childhood. Except for the known association of gross-total resection and improved survival rates, relatively little is known about the clinical and radiographic predictors of recurrent disease and the optimal frequency of surveillance MRI. The authors sought to determine the clinical and radiographic features associated with recurrent or progressive disease in a single-institutional series of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 35 publications
0
27
0
Order By: Relevance
“…The definition for radiographic recurrence was provided in all but two studies [ 10 , 12 ] but again definitions varied between studies. All but one study [ 13 ] reported details of the change in patient management/treatment post-recurrence. Definitions of survival outcome measures were provided in only half of the studies reporting survival, with one study failing to define OS [ 8 ] and one RFS [ 12 ] (see Online Resource 5 for quality assessment table).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The definition for radiographic recurrence was provided in all but two studies [ 10 , 12 ] but again definitions varied between studies. All but one study [ 13 ] reported details of the change in patient management/treatment post-recurrence. Definitions of survival outcome measures were provided in only half of the studies reporting survival, with one study failing to define OS [ 8 ] and one RFS [ 12 ] (see Online Resource 5 for quality assessment table).…”
Section: Resultsmentioning
confidence: 99%
“…The seven studies were published between 2001 and 2016 with six published since 2009 [ 9 14 ]. Five studies were undertaken in the USA [ 8 , 9 , 11 13 ], one in Canada [ 14 ] and one in Australia [ 10 ]. The studies (overall n = 469 patients) were comprised of six low grade tumour studies [ 9 14 ] and one with a mix of low and high-grade tumours [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Repeated relapse/progressive disease in children with LGG is common in incompletely resected/unresectable tumors. Children whose tumour involves the optic tract, those with multifocal tumors, those below 1 year of age and/ or those with evidence of dissemination at initial diagnosis tend to have a higher rate of progression than those with a single lesion …”
Section: Treatmentmentioning
confidence: 99%
“…The impact of surveillance imaging has been assessed in children with different types of malignant CNS tumours including low- and high-grade gliomas [57], medulloblastoma [6, 810], ependymoma, [11] and central nervous system primitive neuroectodermal tumours (CNS-PNETs) [12]. However, differences in imaging schedules and modalities (including both computerised tomography (CT) and MRI), and a reliance upon case series studies, mean no consensus has been reached regarding the utility of surveillance imaging, the optimal interval for undertaking scans or the length of surveillance following diagnosis.…”
Section: Introductionmentioning
confidence: 99%